2013
DOI: 10.1007/978-3-642-41184-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gait Biometrics under Spoofing Attacks

Abstract: Abstract. Gait is a relatively new biometric modality which has a precious advantage over other modalities, such as iris and voice, in that it can be easily captured from a distance. While it has recently become a topic of great interest in biometric research, there has been little investigation into gait spoofing attacks where a person tries to imitate the clothing or walking style of someone else. We recently analysed for the first time the effects of spoofing attacks on silhouette based gait biometric syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This is because of the potential to overcome the limitations of major traditional and well established biometric solutions. This includes concealing biometric signature to spoofing attacks [7, 8]. There has been a large body of research on the use of gait biometrics into surveillance scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…This is because of the potential to overcome the limitations of major traditional and well established biometric solutions. This includes concealing biometric signature to spoofing attacks [7, 8]. There has been a large body of research on the use of gait biometrics into surveillance scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…Spoofing attacks on Video-based gait authentication. Hadid et al [165][166][167] showed successful impersonation of video-based gait biometrics. They suggested dividing the silhouette (and the body frame) into components and verifying each component separately.…”
Section: Vulnerabilities Of Gait-based Biometricsmentioning
confidence: 99%
“…They concluded that it is possible to spoof someone's silhouettes, unlike the conclusion of Gafurov's work. Thus, Hadid et al proposed an anti-spoofing method in their another work [19]. This method first divides a given silhouette into multiple horizontal portions and next computes Local Binary Patterns from Three Orthogonal Planes (LBP-TOP) for each portion, which are then concatenated into a single histogram vector.…”
Section: Studies On Anti-spoofing For Gait Recognitionmentioning
confidence: 99%
“…In the past dozen years, a few studies have tackled the problem of spoofing attacks against gait recognition [18], [19]. However, their focus was not media clonebased spoofing but physical spoofing; that is, they only focused on the gait spoofing attack where an attacker physically tries to imitate clothes or walking style of a target person.…”
Section: Introductionmentioning
confidence: 99%